Survey of Thai Commercial Food Products That Have Been Reported to Contain No Wheat, Rye, Barley, or Gluten According to Their Labels. (22nd November 2019) - Surojanametakul, Vipa; Srikulnath, Sirinrat; Chamnansin, Pailin; Shoji, Masahiro; Tamura, Hirotoshi
Abstract: Celiac disease (CD) and gluten-related disorders are significant health and social issues in Western countries, and CD individuals need to exclude gluten from their diets. The adverse health impacts of CD have extended to Asian countries in which CD was not a problem previously. Thai commercial food products that do not contain wheat, rye, barley, or gluten on their labels were surveyed as to whether they were suitable for CD individuals by examining the absence of gluten or the presence of gluten <20 ppm. In Thailand, ELISA tested for gluten content in 129 commercial food products that contained neither wheat, rye, barley, nor gluten on their labels. One hundred nineteen of these 129 products included <20 ppm gluten, and 10 products contained >20 ppm gluten. Surprisingly, four products showed gluten levels >1%. In these 10 products, wheat presence was confirmed by PCR analysis. Our survey suggests that CD individuals can consume most of the examined Thai food products, and the survey showed the potential of these Thai products as new diets for CD patients so as toexpand the limited food choices from different food cultures, and ultimately to improve the quality of life for all CD individuals globally. The appropriate gluten management strategies need to be implemented by Thai food manufacturers to ensure accurate labeling and to protect the safety of consumers with CD.